Silicon-containing bottom anti-reflection coating composition as well as preparation method and application thereof

By using the use of silicon -containing anti -reflex coating compositions in the light engraving technology, the problem of poor anti -reflected coating and photoretime adhesion in existing technologies, significantly improved the formation effect of the photorettic glue pattern and semiconductor device. Processing performance.

CN119331250APending Publication Date: 2025-01-21FUJIAN HONGGUANG SEMICON MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411584398.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The silicon-containing antireflective coating in the prior art has poor adhesion to the photoresist, which affects the formation effect of the photoresist pattern.

Method used

A silicon-containing bottom anti-reflective coating composition is used. The composition is composed of polymer A and polymer B of a specific structure. Polymer A contains cyano structural units, and polymer B contains fluorine structural units. Through heat exchange The combination of coupling agent, photoacid generator, surfactant and organic solvent improves the adhesion between the anti-reflective film and the photoresist.

Benefits of technology

The light -engraved glue pattern after the development is not easy to collapse, and the effect is good. The anti -reflective membrane has good anti -reflective performance and etching rate, which improves the resolution and line width of the light -carved pattern during the processing of semiconductor device processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331250A_ABST
    Figure CN119331250A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoetching materials, and particularly relates to a silicon-containing bottom anti-reflection coating composition and a preparation method and application thereof. The silicon-containing bottom anti-reflection coating composition at least contains a polymer A and a polymer B, the polymer A contains a structural unit I derived from a first monomer as shown in a free formula (1), an optional structural unit II derived from a second monomer as shown in a free formula (2) and an optional structural unit III derived from a third monomer as shown in a free formula (3); the polymer B contains a fourth structural unit derived from a fourth monomer as shown in a free formula (4) and an optional fifth structural unit derived from a fifth monomer as shown in a free formula (5). The bottom anti-reflection coating composition is characterized in that the polymer A and the polymer B with specific structures are introduced into the bottom anti-reflection coating composition, the adhesion between a formed anti-reflection film and the surface of photoresist is good due to the combined action of cyano groups and fluorine groups, developed photoresist patterns are not prone to collapse, and the forming effect is good. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photolithography materials, and in particular relates to a silicon-containing bottom anti-reflective coating composition and a preparation method and application thereof. Background Art

[0002] Photolithography is a common technology used to perform micro-machining of semiconductor components during the manufacturing process of semiconductor devices. Photolithography is to form a photoresist film on a semiconductor substrate, lay a mask of the target pattern on the photoresist film, and then expose and develop the photoresist pattern by irradiating active light such as ultraviolet rays, and then use the obtained photoresist pattern as a mask to etch the semiconductor substrate to obtain the desired pattern on the semiconductor substrate.

[0003] With the high-speed development and refinement of integrated circuits, the active light used for exposure has also changed from KRF excimer laser (248nm) to ARF excimer laser (193nm), F2 excimer (157nm), extreme ultraviolet laser (EUV), electron light, X-rays and other short wavelengths. In order to obtain ultra-fine photoresist patterns, a three-layer process is often used: spin-coating a layer of spin-coated carbon coating (SOC) with a high carbon content on the semiconductor substrate, spin-coating a layer of organic anti-reflective coating (Barc) on top of the spin-coated carbon coating to eliminate the standing wave phenomenon caused by the refraction and reflection of light during the exposure process of the photoresist, and spin-coating a photoresist layer on the organic anti-reflective coating. As an organic anti-reflective coating, it generally has to have a certain absorbance to light, and is not miscible with the photoresist, has stable performance, and has an etching rate greater than the etching rate of the photoresist. In organic anti-reflective coating compositions, silicon-containing polymers have a high etching rate and can eliminate the standing wave phenomenon in the pattern. However, such silicon-containing polymers have poor storage stability, unstable film thickness during actual use, and poor adhesion to the photoresist. The photoresist pattern formed will be non-vertical, have tailing, and have a large line width roughness (LWR). Summary of the invention

[0004] The purpose of the present invention is to provide a silicon-containing bottom anti-reflective coating composition and a preparation method and application thereof, in view of the problem that the organic silicon anti-reflective composition in the prior art has poor adhesion between the anti-reflective coating and the photoresist, thereby affecting the photoresist pattern forming effect. On the basis of having excellent anti-reflective performance, the adhesion between the anti-reflective coating and the photoresist is improved, and the photoresist pattern forming effect after development is improved.

[0005] In a first aspect, the present invention provides a silicon-containing bottom anti-reflective coating composition.

[0006] Specifically, the silicon-containing bottom anti-reflective coating composition contains at least a polymer A and a polymer B; the polymer A contains a structural unit 1 derived from a first monomer as shown in formula (1) and optionally a structural unit 2 derived from a second monomer as shown in formula (2) and optionally a structural unit 3 derived from a third monomer as shown in formula (3); the polymer B contains a structural unit 4 derived from a fourth monomer as shown in formula (4) and optionally a structural unit 5 derived from a fifth monomer as shown in formula (5);

[0007]

[0008] In formula (1), R 11 For-R 11 `-、-R 11 ``-、-R 11 `-R 11 ``-or-R 11 ``-R 11 `-, R 11 ` is a C1-C6 alkylene group, R 11 `` is C3~C 12 The cyclic alkylene group, R 12 , R 13 , R 14 , R 15 , R 16 At least one of them is a cyano group and the others are independently hydrogen atoms or C1-C3 alkyl groups, at least two of R2, R3, and R4 are C1-C5 alkoxy groups or hydroxy groups and the others are C1-C5 alkyl groups;

[0009] In formula (2), R1' is a C1-C5 alkyl group, at least two of R2', R3', and R4' are C1-C5 alkoxy groups and the rest are C1-C5 alkyl groups or hydroxy groups;

[0010] In formula (3), at least two of R2``, R3``, and R4`` are C1-C5 alkoxy or hydroxy groups and the rest are C1-C5 alkyl groups;

[0011] In formula (4), R 21 C1~C6 alkylene, C3~C 12 Cyclic alkylene, C3~C 12 Cyclic alkenylene or C6~C 20 The aromatic group, R 22 is a C1-C5 alkyl group substituted with F, at least two of R5, R6 and R7 are C1-C5 alkoxy or hydroxy groups and the rest are C1-C5 alkyl groups;

[0012] In formula (5), at least two of R5ˋ, R6ˋ, and R7ˋ are C1-C5 alkoxy groups or hydroxy groups and the rest are C1-C5 alkyl groups, and R8 is C1-C5 alkyl group or C1-C5 alkoxy group.

[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned silicon-containing bottom anti-reflective coating composition, which comprises: mixing the polymer A and polymer B and an optional thermal crosslinking agent, a photoacid generator, a surfactant, and an organic solvent to obtain a silicon-containing bottom anti-reflective coating composition.

[0014] In a third aspect, the present invention also provides the use of the above silicon-containing bottom anti-reflective coating composition in the production of semiconductor devices.

[0015] The key to the present invention is that polymer A and polymer B with specific structures are introduced into the bottom anti-reflection coating composition. Due to the interaction between the cyano group contained in the polymer A and the fluorine group contained in the polymer B, the anti-reflection film formed by curing the bottom anti-reflection coating composition after heating has good adhesion to the photoresist surface, and the photoresist pattern after development is not easy to collapse and has a good formation effect. At the same time, the anti-reflection film has good anti-reflection performance and excellent anti-etching rate, which is beneficial to improving the resolution of the photoresist pattern in the processing of semiconductor devices and reducing the line width roughness of the photoresist pattern, and has good application prospects. DETAILED DESCRIPTION

[0016] The silicon-containing bottom anti-reflective coating composition provided by the present invention contains at least a polymer A and a polymer B; the polymer A contains a structural unit 1 derived from a first monomer as shown in formula (1) and optionally a structural unit 2 derived from a second monomer as shown in formula (2) and optionally a structural unit 3 derived from a third monomer as shown in formula (3); the polymer B contains a structural unit 4 derived from a fourth monomer as shown in formula (4) and optionally a structural unit 5 derived from a fifth monomer as shown in formula (5);

[0017]

[0018] In formula (1), R 11 For-R 11 `-、-R 11 ``-、-R 11 `-R 11 ``-or-R 11 ``-R 11 `-, R 11 ` is a C1-C6 alkylene group, R 11 `` is C3~C 12 The cyclic alkylene group, R 12 , R 13 , R 14 , R15 , R 16 At least one of them is a cyano group and the others are independently hydrogen atoms or C1-C3 alkyl groups, at least two of R2, R3, and R4 are C1-C5 alkoxy groups or hydroxy groups and the others are C1-C5 alkyl groups. In formula (2), R1` is a C1-C5 alkyl group, at least two of R2`, R3`, and R4` are C1-C5 alkoxy groups or hydroxy groups and the others are C1-C5 alkyl groups. In formula (3), at least two of R2`, R3`, and R4` are C1-C5 alkoxy groups or hydroxy groups and the others are C1-C5 alkyl groups. In formula (4), R 21 C1~C6 alkylene, C3~C 12 Cyclic alkylene, C3~C 12 Cyclic alkenylene or C6~C 20 The aromatic group, R 22 is a C1-C5 alkyl group substituted with F, at least two of R5, R6, and R7 are C1-C5 alkoxy groups or hydroxy groups and the rest are C1-C5 alkyl groups. In formula (5), at least two of R5', R6', and R7' are C1-C5 alkoxy groups or hydroxy groups and the rest are C1-C5 alkyl groups, and R8 is a C1-C5 alkyl group or a C1-C5 alkoxy group.

[0019] Specific examples of the C1-C6 alkylene group include, but are not limited to, one of methylene, ethylene, n-propylene, isopropylene, n-butylene, tert-butylene, isobutylene, n-pentylene, isopentylene, tert-pentylene, neopentylene, and hexylene. 12 Specific examples of the cyclic alkylene group include, but are not limited to, one of cyclopropylene, cyclobutylene, cyclopentylene, cyclohexylene, cyclopentylenemethyl, cyclohexylenemethyl, cyclooctylene, and adamantylene. Specific examples of the C1-C3 alkyl group include, but are not limited to, one of methyl, ethyl, n-propyl, and isopropyl. Specific examples of the C1-C5 alkoxy group include, but are not limited to, one of methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentyloxy, isopentyloxy, tert-pentyloxy, and neopentyloxy. Specific examples of the C1-C5 alkyl group include, but are not limited to, one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, and neopentyl. The C3-C 12 Specific examples of the cyclic alkenylene group include, but are not limited to, one of cyclopentenylene, cyclohexenylene, cyclohexenylenemethyl, and cyclooctenylene. 20 Specific examples of the aromatic group include, but are not limited to, one of phenylene, tolylene, ethylenephenylene, biphenylene, tolylene, triphenylene, naphthylene, and anthracene. 22It is a C1-C5 alkyl group substituted with F, which may be fully substituted with F or partially substituted with F, and is preferably a C1-C5 alkyl group substituted with F.

[0020] In the present invention, the structural unit 1 is derived from the structure shown in formula (1), wherein two of R2, R3, and R4 may be alkoxy or hydroxyl groups of C1 to C5 and the remaining one may be alkyl group of C1 to C5, or R2, R3, and R4 may all be alkoxy or hydroxyl groups of C1 to C5. The structural unit 1 may be specifically selected from at least one of the structures shown in formula (1-1), formula (1-2), and formula (1-3).

[0021]

[0022] In the present invention, the structural unit 2 is derived from the structure shown in formula (2), wherein R2', R3', and R4' may have two alkoxy groups or hydroxy groups of C1 to C5 and the remaining one may be an alkyl group of C1 to C5, and the structural unit 2 in this case may serve as an end structural unit and / or an intermediate structural unit in the structure of polymer A; or, R2', R3', and R4' may have three alkoxy groups or hydroxy groups of C1 to C5, and the structural unit 2 in this case may serve as an end structural unit and / or an intermediate structural unit in the structure of polymer A. The structural unit 2 may be specifically selected from at least one of the structures shown in formula (2-1), formula (2-2), and formula (2-3).

[0023] In the present invention, the structural unit three is derived from the structure shown in formula (3), wherein R2``, R3``, and R4`` may have two alkoxy groups or hydroxy groups of C1 to C5 and the remaining one may be an alkyl group of C1 to C5. In this case, the structural unit three can serve as an end structural unit and / or an intermediate structural unit in the structure of polymer A; or, R2``, R3``, and R4`` may have three alkoxy groups or hydroxy groups of C1 to C5. In this case, the structural unit three can serve as an end structural unit and / or an intermediate structural unit in the structure of polymer A. The structural unit three can be specifically selected from at least one of the structures shown in formula (3-1), formula (3-2), and formula (3-3). In addition, the specific structures of the various R groups in formulas (1-1) to (1-3), formulas (2-1) to (2-3), and formulas (3-1) to (3-3) are the same as described above and will not be repeated here.

[0024]

[0025] In the present invention, the structural unit four is derived from the structure shown in formula (4), wherein two of R5, R6, and R7 may be C1-C5 alkoxy or hydroxyl groups and the remaining one may be C1-C5 alkyl, or R5, R6, and R7 may all be C1-C5 alkoxy or hydroxyl groups and the remaining one may be C1-C5 alkyl. The structural unit four may be specifically selected from at least one of the structures shown in formula (4-1), formula (4-2), and formula (4-3).

[0026]

[0027] In the present invention, the structural unit five is derived from the structure shown in formula (5), wherein R5`, R6`, and R7` may have two alkoxy groups or hydroxyl groups of C1 to C5 and the remaining one may be an alkyl group of C1 to C5. In this case, the structural unit five can be used as an end structural unit and / or an intermediate structural unit in the structure of polymer B; or, R5`, R6`, and R7` may be three alkoxy groups of C1 to C5. In this case, the structural unit five can be used as an end structural unit and / or an intermediate structural unit in the structure of polymer B. The structural unit five can be specifically selected from at least one of the structures shown in formula (5-1), formula (5-2), and formula (5-3). Among them, the specific structures of the various R groups in formulas (4-1)-(4-3) and formulas (5-1)-(5-3) are the same as described above and will not be repeated here.

[0028]

[0029] In the present invention, in formula (1), formula (2) and formula (3), R 11 Preferably -R 11 `-or-R 11 `-R 11 ``-, R2, R4, R2`, R4`, R2`, R4` are each independently preferably C1-C5 alkoxy, and R3, R3`, R3` are each independently preferably C1-C5 alkoxy or C1-C5 alkyl. In formula (4) and formula (5), R5, R7, R5`, R7` are each independently preferably C1-C5 alkoxy, and R6, R6` are each independently preferably C1-C5 alkoxy or C1-C5 alkyl.

[0030] In some specific embodiments, the structural unit 1 preferably has a structure shown in formula (1-1). The structural unit 2 preferably has a structure shown in formula (2-1). The structural unit 3 preferably has a structure shown in formula (3-1). The structural unit 4 preferably has a structure shown in formula (4-1).

[0031] In the present invention, the molar ratio of the structural unit 1, the structural unit 2 and the structural unit 3 is preferably 1: (0.5-100): (0.5-100). At this time, polymer A has good molecular chain rigidity, which is more conducive to increasing the contact angle between the anti-reflection film and the photoresist surface. The larger the contact angle, the better the adhesion between the anti-reflection film and the photoresist surface, thereby achieving improved adhesion. Taking the molar amount of the structural unit 1 as 1 mol, the molar amount of the structural unit 2 is preferably 0.5-100 mol, such as 0.5 mol, 0.8 mol, 1 mol, 5 mol, 8 mol, 10 mol, 20 mol, 50 mol, 80 mol, 100 mol or any value therebetween; the molar amount of the structural unit 3 is preferably 0.5-100 mol, such as 0.5 mol, 0.8 mol, 1 mol, 5 mol, 8 mol, 10 mol, 20 mol, 50 mol, 80 mol, 100 mol or any value therebetween. The molar ratio of the structural unit four to the structural unit five is preferably 1:(0.01-100), such as 1:0.01, 1:0.05, 1:0.1, 1:0.5, 1:0.8, 1:1, 1:5, 1:10, 1:20, 1:50, 1:80, 1:100 or any value therebetween. At this time, polymer B has good flexibility, and is more conducive to cooperating with polymer A to increase the adhesion of the anti-reflective film to the photoresist surface, so that the developed photoresist pattern is not easy to collapse and has a good forming effect. Within the above preferred range, polymer A and polymer B are respectively obtained by combining structural units with a specific ratio, which is more conducive to improving the adhesion of the silicon-containing bottom anti-reflective coating composition to the photoresist surface, and obtaining a photoresist pattern with a good developing effect.

[0032] In the present invention, the mass ratio of polymer A to polymer B is preferably 1:(2-100), such as 1:2, 1:5, 1:8, 1:10, 1:20, 1:50, 1:80, 1:100 or any value therebetween. The weight average molecular weight of polymer A is preferably 2000-50000Da, such as 2000Da, 5000Da, 8000Da, 10000Da, 20000Da, 30000Da, 40000Da, 50000Da or any value therebetween; PDI is preferably 1.2-5, such as 1.2, 1.5, 2, 3, 4, 5 or any value therebetween. The weight average molecular weight of the polymer B is preferably 500-20000Da, such as 500Da, 1000Da, 2000Da, 5000Da, 8000Da, 10000Da, 15000Da, 20000Da or any value therebetween; the PDI is preferably 1.2-5, such as 1.2, 1.5, 2, 3, 4, 5 or any value therebetween.

[0033] In the present invention, the polymer A is preferably prepared by the following method: a first monomer as shown in formula (1) and optionally a second monomer as shown in formula (2) and a third monomer as shown in formula (3) are subjected to a first polycondensation reaction in the presence of a first catalyst to obtain polymer A. The polymer B is preferably prepared by the following method: a fourth monomer as shown in formula (4) and optionally a fifth monomer as shown in formula (5) are subjected to a second polycondensation reaction in the presence of a second catalyst to obtain polymer B.

[0034] In the present invention, the molar ratio of the first monomer, the second monomer and the third monomer is preferably 1:(0.5-100):(0.5-100). Taking the molar amount of the first monomer as 1 mol, the molar amount of the second monomer is preferably 0.5-100 mol, such as 0.5 mol, 0.8 mol, 1 mol, 1.2 mol, 1.5 mol, 2 mol, 5 mol, 10 mol, 20 mol, 50 mol, 80 mol, 100 mol or any value therebetween; the molar amount of the third monomer is preferably 0.5-100 mol, such as 0.5 mol, 0.8 mol, 1 mol, 1.2 mol, 1.5 mol, 2 mol, 5 mol, 10 mol, 20 mol, 50 mol, 80 mol, 100 mol or any value therebetween. When the molar ratio of the first monomer, the second monomer, and the third monomer is controlled within the above preferred range, the polymer A obtained thereby has good molecular chain rigidity, which is more conducive to increasing the contact angle between the anti-reflection film and the photoresist surface. The larger the contact angle, the better the adhesion between the anti-reflection film and the photoresist surface, thereby improving the adhesion between the anti-reflection film and the photoresist surface. The molar ratio of the fourth monomer to the fifth monomer is preferably 1:(0.01-100), such as 1:0.01, 1:0.05, 1:0.1, 1:0.5, 1:0.8, 1:1, 1:5, 1:10, 1:20, 1:50, 1:80, 1:100 or any value therebetween. When the molar ratio of the fourth monomer to the fifth monomer is controlled within the above preferred range, the polymer B obtained thereby has good flexibility, which is more conducive to cooperating with the polymer A to increase the adhesion between the anti-reflection film and the photoresist surface, so that the developed photoresist pattern is not easy to collapse and has a good formation effect.

[0035] In the present invention, the conditions of the first polycondensation reaction and the second polycondensation reaction each independently preferably include: the reaction temperature is preferably 30-205°C, more preferably 45-150°C, such as 45°C, 60, 80°C, 100°C, 120°C, 150°C or any value therebetween; the reaction time is preferably 1-24h, more preferably 4-10h, such as 4h, 5h, 6h, 7h, 8h, 9h, 10h or any value therebetween.

[0036] In the present invention, based on the total mass of all monomer compounds in the reaction system, the amount of the first catalyst and the second catalyst is preferably 0.1 to 10wt%, such as 0.1wt%, 0.5wt%, 1wt%, 2wt%, 5wt%, 10wt% or any value therebetween. The first catalyst and the second catalyst are preferably acidic catalysts and / or alkaline catalysts. The acidic catalyst is preferably an organic acid catalyst and / or an inorganic acid catalyst. Among them, specific examples of the organic acid catalyst include but are not limited to: at least one of oxalic acid, toluenesulfonic acid, benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, citric acid, tartaric acid, salicylic acid, itaconic acid, and maleic acid; specific examples of the inorganic acid catalyst include but are not limited to: at least one of hydrochloric acid, nitric acid, sulfuric acid, perchloric acid, and phosphoric acid. Specific examples of the base catalyst include, but are not limited to, one of methylamine, ethylamine, propylamine, butylamine, ethylenediamine, hexamethylenediamine, dimethylamine, diethylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, cyclohexylamine, triethanolamine, hexamethylenetetramine, aniline, N,N-dimethylaniline, pyridine, pyrrole, picoline, tetramethylammonium hydroxide, sodium hydroxide, potassium hydroxide, and barium hydroxide.

[0037] In some specific embodiments, the first polycondensation reaction and the second polycondensation reaction are each independently preferably carried out under an inert gas atmosphere. Specific examples of the inert gas include, but are not limited to, at least one of nitrogen, helium, neon and argon.

[0038] In some specific embodiments, the first polycondensation reaction and the second polycondensation reaction are each independently carried out in the presence of an organic solvent, which is more conducive to the contact reaction between the reaction monomers. Specific examples of the organic solvent include, but are not limited to, at least one of benzene, toluene, xylene, propylene glycol diacetate, methyl methoxyacetate, ethyl acetate, butyl acetate, ethyl lactate, dibutyl ether, γ-butyrolactone, and tetrahydrofuran.

[0039] In the present invention, the silicon-containing bottom anti-reflective coating composition preferably contains polymer A, polymer B, a thermal crosslinking agent, a photoacid generator, a surfactant and an organic solvent. Based on the total mass of the anti-reflective coating composition, the content of the polymer A is preferably 0.1-99wt%, such as 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 20wt%, 50wt%, 70wt%, 90wt%, 99wt% or any value therebetween; the content of the polymer B is preferably 0.1-99wt%, such as 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 20wt%, 50wt%, 70wt%, 90wt%, 99wt% or any value therebetween; the content of the thermal crosslinking agent is preferably 0.01-0.5wt%, such as 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% t% or any value therebetween; the content of the photoacid generator is preferably 0.01-0.5wt%, such as 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or any value therebetween; the content of the surfactant is preferably 0.005-0.05wt%, such as 0.005wt%, 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt% or any value therebetween; the content of the organic solvent is preferably 0.1-99wt%, such as 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 20wt%, 50wt%, 70wt%, 90wt%, 99wt% or any value therebetween.

[0040] In the present invention, the thermal crosslinking agent can be a conventional choice in the art, preferably at least one selected from sulfonium compounds, iodonium compounds and ammonium compounds. Specific examples of the sulfonium compounds include, but are not limited to, at least one of triphenylsulfonium formate, triphenylsulfonium acetate, triphenylsulfonium linolenate, triphenylsulfonium stearate, triphenylsulfonium benzoate, triphenylsulfonium benzoate, triphenylsulfonium salicylate, triphenylsulfonium trifluoroformate, triphenylsulfonium trifluoroacetate, triphenylsulfonium maleate, triphenylsulfonium nitrate and triphenylsulfonium citrate. Specific examples of the iodonium compound include, but are not limited to, at least one of diphenyliodonium formate, diphenyliodonium acetate, diphenyliodonium propionate, diphenyliodonium diformate, diphenyliodonium isophthalate, diphenyliodonium terephthalate, diphenyliodonium salicylate, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium trifluoroacetate, diphenyliodonium itaconate, diphenyliodonium maleate, diphenyliodonium fumarate, and diphenyliodonium citrate. Specific examples of the ammonium compound include, but are not limited to, at least one of tetramethylammonium acid, tetramethylammonium acetate, tetramethylammonium propionate, tetramethylammonium oleate, tetramethylammonium stearate, tetramethylammonium linoleate, tetramethylammonium linolenate, tetramethylammonium benzoate, tetramethylammonium fumarate, tetramethylammonium citrate, tetramethylammonium bromide, and tetramethylammonium iodide.

[0041] In the present invention, the photoacid generator can be a conventional choice in the art, preferably at least one selected from onium salt compounds, diazomethane derivatives, glyoxime derivatives, bissulfone derivatives, nitrobenzyl sulfonate derivatives and sulfonic acid derivatives. Wherein, specific examples of the onium salt compounds include but are not limited to: at least one of diphenyl iodonium trifluoromethanesulfonate, diphenyl iodonium p-toluenesulfonate, triphenyl sulfonium trifluoromethanesulfonate, diphenyl sulfonium trifluoromethanesulfonate, triphenyl sulfonium p-toluenesulfonate, diphenyl sulfonium p-toluenesulfonate, triphenyl sulfonium nonafluorobutanesulfonate, triphenyl sulfonium butanesulfonate, trimethyl sulfonium trifluoromethanesulfonate and trimethyl sulfonium p-toluenesulfonate. Specific examples of the diazomethane derivatives include, but are not limited to, at least one of bis(benzenesulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, bis(xylenesulfonyl)diazomethane, bis(cyclohexylsulfonyl)diazomethane, bis(n-butylsulfonyl)diazomethane, bis(isobutylsulfonyl)diazomethane, and 1-cyclohexylsulfonyl-1-(tert-butylsulfonyl)diazomethane. Specific examples of the glyoxime derivatives include, but are not limited to, at least one of bis-o-(p-toluenesulfonyl)-α-dimethylglyoxime, bis-o-(p-toluenesulfonyl)-α-diphenylglyoxime, bis-o-(p-toluenesulfonyl)-α-dicyclohexylglyoxime, bis-o-(trifluoromethanesulfonyl)-α-dimethylglyoxime, bis-o-(methanesulfonyl)-α-dimethylglyoxime, and bis-o-(camphorsulfonyl)-α-dimethylglyoxime. Specific examples of the bissulfone derivatives include, but are not limited to, at least one of bis-naphthylsulfonylmethane, bis-trifluoromethylsulfonylmethane, bis-methylsulfonylmethane, bis-ethylsulfonylmethane, bis-propylsulfonylmethane, bis-isopropylsulfonylmethane, and bis-p-toluenesulfonylmethane. Specific examples of the nitrobenzyl sulfonate derivatives include, but are not limited to, 2,6-dinitrobenzyl p-toluenesulfonate and / or 2,4-dinitrobenzyl p-toluenesulfonate. Specific examples of the sulfonic acid derivatives include, but are not limited to, at least one of N-hydroxysuccinimide methane sulfonate, N-hydroxysuccinimide trifluoromethane sulfonate, N-hydroxysuccinimide ethane sulfonate, N-hydroxysuccinimide 1-propane sulfonate, N-hydroxysuccinimide-2-propane sulfonate, N-hydroxysuccinimide p-toluenesulfonate, N-hydroxysuccinimide methoxytoluenesulfonate, N-hydroxy-5-norbornene-2,3-dicarboxyimide methane sulfonate, N-hydroxy-5-norbornene-2,3-dicarboxyimide trifluoromethane sulfonate, and N-hydroxy-5-norbornene-2,3-dicarboxyimide p-toluenesulfonate.

[0042] In the present invention, the surfactant can be a conventional choice in the art, preferably at least one selected from polyoxyethylene alkyl aryl ether compounds, sorbitan fatty acid ester compounds and polyoxyethylene sorbitan fatty acid ester compounds.

[0043] In the present invention, the organic solvent can be a conventional choice in the art, preferably at least one selected from benzene, toluene, xylene, acetone, methanol, ethanol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, ethylene glycol monohexyl ether, diethylene glycol monohexyl ether, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol diacetate, methyl methoxyacetate, ethyl acetate, butyl acetate, ethyl lactate, dibutyl ether, tetrahydrofuran and γ-butyrolactone.

[0044] The present invention provides a method for preparing the silicon-containing bottom anti-reflective coating composition, which comprises: mixing polymer A and polymer B and optional thermal crosslinking agent, photoacid generator, surfactant and organic solvent to obtain the silicon-containing bottom anti-reflective coating composition.

[0045] The present invention also provides a method for forming a photoresist pattern, which comprises: applying a spin-on carbon (SOC) composition on a substrate, thermally curing to obtain a spin-on carbon organic film, spin-coating a silicon-containing organic anti-reflective composition on the spin-on carbon organic film, thermally curing to obtain a bottom anti-reflective coating, spin-coating a photoresist on the bottom anti-reflective coating, baking to form a photoresist coating, and then obtaining a photoresist pattern through exposure and development processes. The conditions for thermal curing include: the temperature is preferably 100 to 250° C., such as 100° C., 120° C., 150° C., 180° C., 200° C., 250° C. or any value therebetween; the time is preferably 0.5 to 5 min, such as 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min or any value therebetween. The spin-on carbon (SOC) composition and the photoresist can be a type of substance commonly used in the art.

[0046] The present invention will be described in detail below by specific examples. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0047] Synthesis Example 1 Synthesis of the First Monomer H1

[0048] Take 18.028g (0.1mol) of monomer Da1 and 17.96g (0.1mol) of monomer Db1 in a three-necked flask, add 200mL of tetrahydrofuran, heat to reflux at 60°C under nitrogen environment protection, stop heating after 8h, cool the reaction solution to room temperature to obtain a light yellow liquid, remove excess solvent through a rotary evaporator, and sink the remaining yellow liquid into water to obtain a light yellow solid, which is the first monomer H1 (323.42).

[0049] The structures of the monomers Da1, Db1, and the first monomer H1 are shown below.

[0050]

[0051] The first monomer H1 13 C-NMR DMSO detection results are: 113.2(1C), 146.4(1C), 127.8(1C), 133.0(1C), 129.6(1C), 134.1(1C), 10.9(1C), 165.9(1C), 68.0(1C), 50.2(3C), 115.8(1C), 20.1(1C), 13.1(1C).

[0052] Synthesis Example 2 Synthesis of the First Monomer H2

[0053] The first monomer H2 was synthesized according to the method of Synthesis Example 1, except that the same molar amount of monomer Da2 was used instead of monomer Da1. The other conditions were the same as those of Synthesis Example 1. The light yellow solid obtained was the first monomer H2 (391.54).

[0054] The structures of monomers Da2, Db1, and first monomer H2 are shown below.

[0055]

[0056] The first monomer H2 13 C-NMR DMSO detection results are: 72.9(1C), 113.2(1C), 146.4(1C), 127.8(1C), 133.0(1C), 129.6(1C), 134.1(1C), 33.4(1C), 39.0(1C), 31.4(1C), 33.3(1C), 22.7(1C), 13.6(1C), 165.9(1C), 50.2(3C), 115.8(1C), 19.2(1C), 20.1(1C).

[0057] Synthesis Example 3 Synthesis of the First Monomer H3

[0058] The first monomer H3 was synthesized according to the method of Synthesis Example 1, except that the same molar amount of monomer Da3 was used instead of monomer Da1. The other conditions were the same as those of Synthesis Example 1. The light yellow solid obtained was the first monomer H3 (391.54).

[0059] The structures of monomers Da3, Db1, and the first monomer H3 are shown below.

[0060] The first monomer H3 13 C-NMR DMSO detection results are: 70.9(1C), 113.2(1C), 146.4(1C), 127.8(1C), 133.0(1C), 129.6(1C), 134.1(1C), 39.4(1C), 31.0(2C), 29.4(2C), 13.6(1C), 165.9(1C), 50.2(3C), 115.8(1C), 19.2(1C), 20.1(1C).

[0061]

[0062] Synthesis Example 4 Synthesis of the First Monomer H4

[0063] The first monomer H4 was synthesized according to the method of Synthesis Example 1, except that the same molar amount of monomer Da4 was used instead of monomer Da1. The other conditions were the same as those of Synthesis Example 1. The light yellow solid obtained was the first monomer H4 (550.68).

[0064] The structures of monomers Da4, Db1, and the first monomer H4 are shown below.

[0065]

[0066] The first monomer H4 13 C-NMR DMSO detection results are: 76.2(1C), 78.7(1C), 113.2(2C), 146.4(2C), 127.8(2C), 133.0(2C), 129.6(2C), 134.1(2C), 33.4(1C), 33.0(1C), 25.0(1C), 29.4(1C), 13.6(1C), 165.9(2C), 50.2(3C), 115.8(2C), 19.2(1C), 20.1(2C).

[0067] Synthesis Example 5 Synthesis of the First Monomer H5

[0068] The first monomer H5 was synthesized according to the method of Synthesis Example 1, except that the same molar amount of monomer Db2 was used instead of monomer Db1. The other conditions were the same as those of Synthesis Example 1. The light yellow solid obtained was the first monomer H5 (337.45).

[0069] The structures of monomers Da1, Db2, and the first monomer H5 are shown below.

[0070]

[0071] The first monomer H5 13 C-NMR DMSO detection results are: 148.5(1C), 137.4(1C), 113.1(1C), 127.7(1C), 130.0(1C), 136.2(1C), 10.9(1C), 165.9(1C), 68.0(1C), 50.2(3C), 115.8(1C), 19.6(1C), 18.3(1C), 13.1(1C).

[0072] Synthesis Example 6 Synthesis of the First Monomer H6

[0073] The first monomer H6 was synthesized according to the method of Synthesis Example 5, except that the same molar amount of monomer Da2 was used instead of monomer Da1. The other conditions were the same as those of Synthesis Example 5. The light yellow solid obtained was the first monomer H6 (405.57).

[0074] The structures of monomers Da2, Db2, and the first monomer H6 are shown below.

[0075]

[0076] The first monomer H6 13 C-NMR DMSO detection results are: 72.9(1C), 148.5(1C), 137.4(1C), 113.1(1C), 127.7(1C), 130.0(1C), 136.2(1C), 33.4(1C), 39.0(1C), 31.4(1C), 33.3(1C), 22.7(1C), 13.6(1C), 165.9(1C), 50.2(3C), 115.8(1C), 19.2(1C), 19.6(1C), 18.3(1C).

[0077] Preparation Examples 1 to 8 Preparation of Polymer A

[0078] Weigh 0.1 mol of the first monomers H1 to H6 obtained in Synthesis Examples 1 to 6 respectively, mix with 13.622 g (0.1 mol) of methyltrimethoxysilane (third monomer), 19.829 g (0.1 mol) of phenyltrimethoxysilane (second monomer), 154 g of tetrahydrofuran, 0.6811 g of hydrochloric acid and 5 g of deionized water, heat to 50° C. in a nitrogen atmosphere and react at this temperature for 12 hours, add 200 g of propylene glycol ethyl ether after the reaction is completed, mix evenly, and obtain polymer A by vacuum distillation. The added mass of the first monomers H1 to H6 obtained in Synthesis Examples 1 to 6 and the weight average molecular weight Mw and PDI results of the prepared polymer A are specifically shown in Table 1.

[0079] Table 1

[0080]

[0081]

[0082] Preparation Examples 9 to 12 and Comparative Preparation Examples 1 to 2 Preparation of Polymer B

[0083] A certain mass of the fourth monomer and the fifth monomer were weighed respectively, mixed with 154 g of tetrahydrofuran, 0.6811 g of hydrochloric acid and 5 g of deionized water, heated to 50° C. in a nitrogen atmosphere and reacted at this temperature for 12 h, and after the reaction, 200 g of propylene glycol ethyl ether was added and mixed evenly, and polymer B was obtained by reduced pressure distillation. Among them, the specific component names and addition masses of the fourth monomer and the fifth monomer, as well as the weight average molecular weight Mw and PDI results of the prepared polymer B are specifically shown in Table 2.

[0084] Table 2

[0085]

[0086]

[0087] Among them, trimethoxy((4-trifluoromethyl)benzyl)silane has the following structure:

[0088]

[0089] Preparation of Silicon-Containing Bottom Anti-Reflective Coating Compositions in Examples 1 to 14 and Comparative Examples 1 to 4

[0090] 15 parts by weight of polymer A, 85 parts by weight of polymer B, 1 part by weight of thermal crosslinking agent, 1 part by weight of photoacid generator triphenylsulfonium perfluorobutanesulfonate, 0.8 parts by weight of surfactant FC4430 and 8000 parts by weight of propylene glycol ethyl ether were mixed uniformly to obtain a bottom anti-reflective coating. The specific components of polymer A, polymer B and thermal crosslinking agent added in Examples 1 to 14 and Comparative Examples 1 to 4 are shown in Table 3.

[0091] Table 3

[0092]

[0093]

[0094] Test Case

[0095] 1. The silicon-containing bottom anti-reflective coating composition obtained in the above Examples 1 to 14 and Comparative Examples 1 to 4 was applied on a silicon wafer, baked at 200° C. for 120 seconds, and cured to form an anti-reflective film. The relevant performance tests were performed according to the following method. The results are shown in Table 4:

[0096] (1) An ellipsometer (JA Woolam, VUV-303) was used to measure the refractive index n, extinction coefficient k and film thickness of the antireflection film at 193 nm.

[0097] (2) Use a contact angle meter (KRUSS, DSA100L) to test the contact angle of the anti-reflection film.

[0098] (3) A dry etching device TE-8500P manufactured by Tokyo Electron was used to etch the anti-reflective film with CHF3 / CF4 gas, and the etching rate was tested. The etching conditions specifically include: a processing chamber pressure of 40 Pa, a PF power of 1300 W, a gap of 9 mm, a CHF3 gas flow rate of 30 mL / min, a CF4 gas flow rate of 30 mL / min, an Ar gas flow rate of 100 mL / min, and an etching time of 10 s.

[0099] Table 4

[0100]

[0101]

[0102] 2. Performance evaluation of photoresist pattern: First, SOC was spin-coated on a silicon wafer and heated at 220°C for 60s to form a spin-coated carbon organic film. Then, the organic silicon polymers obtained in Examples 1 to 12 and Comparative Examples 1 to 2 were spin-coated on the spin-coated carbon organic film and heated at 200°C for 60s to form a silicon-containing antireflection film (Film1 to Film9). Then, a positive photoresist (PR-1) was spin-coated on the silicon-containing antireflection film and heated at 100°C for 90s to form a photoresist film. An ArF exposure device (manufactured by NIKON) was used. The photoresist pattern was exposed by a 2.38% tetramethylammonium hydroxide aqueous solution (S305B), heated at 110°C for 90s (PEB), and then developed with a 2.38% tetramethylammonium hydroxide aqueous solution to form a positive photoresist pattern with a line width of 0.13μm. The size of the obtained photoresist pattern was measured by an electron microscope (CG6300) manufactured by Hitachi High-Technologies Corporation, the pattern collapse and cross-sectional shape were measured by an electron microscope (S4700) manufactured by Hitachi, and the line width roughness (LWR) was measured by an electron microscope (CG4000) manufactured by Hitachi High-Technologies Corporation. The results are shown in Table 5.

[0103] The composition of the PR-1 polymer is: 1 part by weight of polymer W1, 0.05 parts by weight of photoacid generator PAG1, 0.01 parts by weight of quencher Q1, and 2.5 parts by weight of solvent PGMEA.

[0104] The polymer W1 has a structure shown in formula (I), m:n=0.4:0.6, molecular weight Mw=8800 g / mol, PDI=1.81. The photoacid generator PAG1 has a structure shown in formula (II). The quencher Q1 has a structure shown in formula (III).

[0105]

[0106] Table 5

[0107] Group Silicone anti-reflective film ArF photoresist Pattern shape after development Pattern collapse Example 1 Film1 PR-1 Vertical Shape No collapse Example 2 Film2 PR-1 Vertical Shape No collapse Example 3 Film3 PR-1 Vertical Shape No collapse Example 4 Film4 PR-1 Vertical Shape No collapse Example 5 Film5 PR-1 Vertical Shape No collapse Example 6 Film6 PR-1 Vertical Shape No collapse Example 7 Film7 PR-1 Vertical Shape No collapse Example 8 Film8 PR-1 Vertical Shape No collapse Example 9 Film9 PR-1 Vertical Shape No collapse Example 10 Film10 PR-1 Vertical Shape No collapse Embodiment 11 Film11 PR-1 Vertical Shape No collapse Example 12 Film12 PR-1 Vertical Shape No collapse Embodiment 13 Film13 PR-1 Vertical Shape No collapse Embodiment 14 Film14 PR-1 Vertical Shape No collapse Comparative Example 1 Film15 PR-1 Vertical Shape have Comparative Example 2 Film16 PR-1 Vertical Shape have Comparative Example 3 Film17 PR-1 Vertical Shape have Comparative Example 4 Film18 PR-1 Vertical Shape have

[0108] It can be seen from the results of Table 4 and Table 5 that, compared with Comparative Examples 1-4, the anti-reflection film formed by the silicon-containing bottom anti-reflection coating composition provided by the present invention has a larger front contact angle, indicating that it has good hydrophobicity, and the photoresist pattern after development has a good shape and no collapse, and also has a higher refractive index and extinction coefficient, good anti-reflection performance, and has an excellent etching rate compatible with the photoresist.

[0109] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A silicon-containing bottom anti-reflective coating composition, characterized in that: The silicon-containing bottom anti-reflective coating composition contains at least a polymer A and a polymer B; the polymer A contains a structural unit 1 derived from a first monomer as shown in formula (1) and optionally a structural unit 2 derived from a second monomer as shown in formula (2) and optionally a structural unit 3 derived from a third monomer as shown in formula (3); the polymer B contains a structural unit 4 derived from a fourth monomer as shown in formula (4) and optionally a structural unit 5 derived from a fifth monomer as shown in formula (5); In formula (1), R 11 For-R 11 `-、-R 11 ``-、-R 11 `-R 11 ``-or-R 11 ``-R 11 `-, R 11 ` is a C1-C6 alkylene group, R 11 `` is C3~C 12 The cyclic alkylene group, R 12 , R 13 , R 14 , R 15 , R 16 At least one of them is a cyano group and the others are independently hydrogen atoms or C1-C3 alkyl groups, at least two of R2, R3, and R4 are C1-C5 alkoxy groups or hydroxy groups and the others are C1-C5 alkyl groups; In formula (2), R1' is a C1-C5 alkyl group, at least two of R2', R3', and R4' are C1-C5 alkoxy groups or hydroxyl groups and the rest are C1-C5 alkyl groups; In formula (3), at least two of R2``, R3``, and R4`` are C1-C5 alkoxy or hydroxy groups and the rest are C1-C5 alkyl groups; In formula (4), R 21 C1~C6 alkylene, C3~C 12 Cyclic alkylene, C3~C 12 Cyclic alkenylene or C6~C 20 The aromatic group, R 22 is a C1-C5 alkyl group substituted with F, at least two of R5, R6 and R7 are C1-C5 alkoxy or hydroxy groups and the rest are C1-C5 alkyl groups; In formula (5), at least two of R5ˋ, R6ˋ, and R7ˋ are C1-C5 alkoxy groups or hydroxy groups and the rest are C1-C5 alkyl groups, and R8 is C1-C5 alkyl group or C1-C5 alkoxy group.

2. The silicon-containing bottom anti-reflective coating composition according to claim 1, characterized in that The molar ratio of the structural unit 1, the structural unit 2 and the structural unit 3 is 1:(0.5-100):(0.5-100); Preferably, the molar ratio of the structural unit four to the structural unit five is 1:(0.01-100); Preferably, the mass ratio of polymer A to polymer B is 1:(2-100); Preferably, the weight average molecular weight of the polymer A is 2000-50000 Da, and the PDI is 1.2-5; Preferably, the weight average molecular weight of the polymer B is 500-20000 Da, and the PDI is 1.2-5.

3. The silicon-containing bottom anti-reflective coating composition according to claim 1, characterized in that In formula (1), formula (2) and formula (3), R 11 For-R 11 ˋ-or-R 11 ˋ-R 11 ˋˋ-, R2, R4, R2ˋ, R4ˋ, R2ˋˋ, R4ˋˋ are each independently a C1~C5 alkoxy group, and R3, R3ˋ, R3ˋˋ are each independently a C1~C5 alkoxy group or a C1~C5 alkyl group; in formula (4) and formula (5), R5, R7, R5ˋ, R7ˋ are each independently a C1~C5 alkoxy group, and R6, R6ˋ are each independently a C1~C5 alkoxy group or a C1~C5 alkyl group.

4. The silicon-containing bottom anti-reflective coating composition according to claim 1, characterized in that The polymer A is prepared by the following method: a first monomer as shown in formula (1) and optionally a second monomer as shown in formula (2) and a third monomer as shown in formula (3) are subjected to a first polycondensation reaction in the presence of a first catalyst to obtain polymer A; The polymer B is prepared by the following method: a fourth monomer as shown in formula (4) and an optional fifth monomer as shown in formula (5) are subjected to a second polycondensation reaction in the presence of a second catalyst to obtain the polymer B.

5. The silicon-containing bottom anti-reflective coating composition according to claim 4, characterized in that: The molar ratio of the first monomer, the second monomer, and the third monomer is 1:(0.5-100):(0.5-100); Preferably, the molar ratio of the fourth monomer to the fifth monomer is 1:(0.01-100); Preferably, the conditions of the first polycondensation reaction and the second polycondensation reaction independently include: a reaction temperature of 30 to 205° C., and a reaction time of 1 to 24 h.

6. The silicon-containing bottom anti-reflective coating composition according to claim 4, characterized in that: Based on the total mass of all monomer compounds in the reaction system, the amounts of the first catalyst and the second catalyst are independently 0.1 to 10 wt %; Preferably, the first catalyst and the second catalyst are each independently an acidic catalyst and / or a basic catalyst; Preferably, the acidic catalyst is an organic acid catalyst and / or an inorganic acid catalyst; Preferably, the alkaline catalyst is selected from at least one of methylamine, ethylamine, propylamine, butylamine, ethylenediamine, hexamethylenediamine, dimethylamine, diethylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, cyclohexylamine, triethanolamine, hexamethylenetetramine, aniline, N,N-dimethylaniline, pyridine, pyrrole, picoline, tetramethylammonium hydroxide, sodium hydroxide, potassium hydroxide, and barium hydroxide.

7. The silicon-containing bottom anti-reflective coating composition according to any one of claims 1 to 6, characterized in that: The silicon-containing bottom anti-reflective coating composition contains polymer A, polymer B, a thermal crosslinking agent, a photoacid generator, a surfactant and an organic solvent.

8. The silicon-containing bottom anti-reflective coating composition according to claim 7, characterized in that: Based on the total mass of the anti-reflective coating composition, the content of the polymer A is 0.1 to 99 wt %, the content of the polymer B is 0.1 to 99 wt %, the content of the thermal crosslinking agent is 0.01 to 0.5 wt %, the content of the photoacid generator is 0.01 to 0.5 wt %, the content of the surfactant is 0.005 to 0.05 wt %, and the content of the organic solvent is 0.1 to 99 wt %.

9. A method for preparing a silicon-containing bottom anti-reflective coating composition, characterized in that: The method comprises: mixing the polymer A and polymer B described in any one of claims 1 to 8 and an optional thermal crosslinking agent, a photoacid generator, a surfactant, and an organic solvent to obtain a silicon-containing bottom anti-reflective coating composition.

10. Use of the silicon-containing bottom anti-reflective coating composition according to any one of claims 1 to 8 in the production of semiconductor devices.